Development of inverse replica fixture for nano-finishing of knee joint using R-MRAFF process. Issue 1 (May 2019) - Nagdeve, Leeladhar; Jain, V. K.; Ramkumar, J.
Abstract: Rotational-Magnetorheological Abrasive Flow Finishing (R-MRAFF) process is a technique of nano-finishing in general and free-form/sculptured surfaces in particular. Knee joint is one such example of free-form surface which is used by orthopedic surgeons. Knee joints are usually made of cobalt chromium alloy which is bio-compatible material, and it is difficult to finish. The present work deals with the development of an inverse replica for a knee joint. This inverse replica is used as a fixture so that the fluid can flow with constant velocity within the confined gap between the workpiece and inner surface of the fixture in order to achieve uniform nano-level finish. Using this technique, variation in the surface roughness ( Ra ) over the knee joint surface can be minimized and productivity can be enhanced. The finishing efficiency of the R-MRAFF process depends on the input parameters such as extrusion pressure, number of finishing cycles, rotational speed of the magnet, etc. These parameters should be controlled and optimized for precision finishing which is the main objective of the present research work. The minimum average Ra of 52 nm is achieved from the initial average Ra of 194 nm on the knee joint surface. The percentage change in Ra (73.20%) was achieved using the proposed method.